The Causes and Effects of Mercury and Methylmercury Contamination in the Marine Environment: A Review - Al-Sulaiti, Maetha M.; Soubra, Lama; Al-Ghouti, Mohammad A. (Current pollution reports, 2022)
Purpose of Review The concern of mercury pollution and the impact that it poses on the marine environment were studied heavily since the case of the poison from Minamata bay in the 1960s. The present study provides an insight into the cycle of mercury and methylmercury in the marine environment and the bioindicators that reflect the exposure levels. The paper also used the driving forces, pressures, states, impacts, and responses (DPSIR) analysis to evaluate the global mercury and methylmercury contamination problem. Recent Findings The high global budgets of atmospheric total mercury influence the ocean surface water. Therefore, the aquatic environment contamination level is in turn affected by the surrounding emission sources such as industrial and petroleum activities in addition to the transport and fate of mercury across the environmental compartments. This will increase the mercury levels in fish species and will cause an adverse risk to human health through biomagnification. Summary This review presents a thorough description of mercury sources and emissions and their fate and transport across the different environmental compartments, despite the fact that serious mitigation measures were taken and guidelines were applied. The risk from fish consumption is still a serious concern as a result of the current mercury emissions and stability and persistent characteristics.